PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN LPP TVRI STASIUN SULAWESI SELATAN - Andi Rahmawati; Andi Abdul Razak Ishak; Amat Arba (Sekolah Tinggi Pariwisata Mataram, 2021)
The purpose of this study is to find out the influence of organizational culture and leadership both partially and simultaneously on the performance of employees of LPP TVRI South Sulawesi Station. The types of data used in this study are qualitative and quantitative data. The data sources used are primary and secondary data. The number of samples used as many as 42 people from a population of 276 employees. The analysis methods used are descriptive quantitative, f-test and t-test. The results showed that organizational culture and leadership had a positive and significant effect on employee performance both partially and simultaneously.